2013
DOI: 10.1016/j.aller.2011.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Changes in IL-10 and specific antibodies associated to successful Dermatophagoides pteronyssinus immunotherapy in children during the first year of treatment

Abstract: Thirty-eight children completed the study. At T1 all had rhinitis and 34 also had asthma. At T3, 30 patients had improved, six experienced no changes and two worsened. Improvement was associated to FEV1/FVC and VAS improvement; to a reduction in D. pteronyssinus skin prick test; to a progressive increase in serum levels of D. pteronyssinus IgE, and D. pteronyssinus, Der p1 and Der p2 IgG4. IL-10 levels showed an early increase at T2f (the end of initial build-up immunotherapy phase), and then a reduction at T3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
1
4
0
1
Order By: Relevance
“…Tolerance for the target allergen can be induced through ASIT by the involvement of Tregs and immunosuppressive cytokines . Interleukin‐10, a suppressive chemokine produced by Treg cells, could play an important role in the release of s‐IgG4 and may exert potent suppressive effects on the production of s‐IgE . In this study, we found that serum IL‐10 was significantly increased after 2 years of ASIT, which was in line with other studies showing that HDM and grass pollen immunotherapy could not only induce IL‐10 production, but also suppress clinical symptoms of asthma and AD .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Tolerance for the target allergen can be induced through ASIT by the involvement of Tregs and immunosuppressive cytokines . Interleukin‐10, a suppressive chemokine produced by Treg cells, could play an important role in the release of s‐IgG4 and may exert potent suppressive effects on the production of s‐IgE . In this study, we found that serum IL‐10 was significantly increased after 2 years of ASIT, which was in line with other studies showing that HDM and grass pollen immunotherapy could not only induce IL‐10 production, but also suppress clinical symptoms of asthma and AD .…”
Section: Discussionsupporting
confidence: 90%
“…27 Interleukin-10, a suppressive chemokine produced by Treg cells, could play an important role in the release of s-IgG4 and may exert potent suppressive effects on the production of s-IgE. 28 In this study, we found that serum IL-10 was significantly increased after 2 years of ASIT, which was in line with other studies showing that HDM and grass pollen immunotherapy could not only induce IL-10 production, but also suppress clinical symptoms of asthma and AD. 27,29 Although no correlation between IL-10 expression and POEM score could be demonstrated, the change of s-IgG4 was positively correlated with serum IL-10 levels after ASIT.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also described clinical improvement after SIT. In a prospective, multicenter study of 38 children with D. pteronyssinus rhinitis or asthma, Martín-Muñoz et al [27] found that in more than three quarters of the patients, the symptoms of both rhinitis and asthma improved after 1 year of treatment. Pifferi et al [28] found a significant decrease in asthma exacerbations and a reduction in drug intake after 1 year of treatment in a group of 15 children receiving SIT for D. pteronyssinus .…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study, children with a diagnosis of respiratory allergy to D. pteronyssinus received SCIT during one year. An early IL-10 response with an increase in specific IgG4 levels and an associated beginning of the decline in Der p1 and Der p2 IgE levels were efficacy predictors of the SCIT [51]. A casecontrol study with AIT-treated patients and controls found that allergen-induced basophil activation was significantly higher in patients with seasonal allergic rhinitis, and was inhibited by AIT.…”
Section: Biomarkers/predictor Of Responsementioning
confidence: 99%